2011
DOI: 10.1002/qua.22587
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of tetrahydrofuran: Comparative investigation of spectroscopic and structural properties between gas and liquid phases

Abstract: Rovibrational spectroscopic constant of tetrahydrofuran (THF) dimer have been calculated starting from three potential energy curves, each one obtained in a different way: (i) by ab initio calculations at MP2/aug-cc-pVDZ level; (ii) using Lennard-Jones liquid parameters available in the literature, and (iii) from the pair obtained through Monte Carlo Simulation of liquid THF. The comparison among these results allowed the characterization of many solvent effect contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Here, one should consider that the internal energy after ionization depends on the considered geometry of the neutral dimer. If we assume for the THF dimer geometry instead of the present stacked arrangement a T-like geometry as it was obtained by some groups 33 , then a vertical transition energy of 9.71 eV is obtained which is even closer to the TS-1 energy. The FC region is shown by the yellow bands in Fig.…”
Section: Sample Composition and Characterization Of Reaction Productssupporting
confidence: 58%
“…Here, one should consider that the internal energy after ionization depends on the considered geometry of the neutral dimer. If we assume for the THF dimer geometry instead of the present stacked arrangement a T-like geometry as it was obtained by some groups 33 , then a vertical transition energy of 9.71 eV is obtained which is even closer to the TS-1 energy. The FC region is shown by the yellow bands in Fig.…”
Section: Sample Composition and Characterization Of Reaction Productssupporting
confidence: 58%
“…In contrast, Gargano and co-workers [48] calculated an almost T-like structure. This confirmed the simulations of Bowron et al [49], which showed that the creation of larger clusters is done by T-like packing of the molecules.…”
Section: Resultsmentioning
confidence: 94%
“…Boese et al [ 39 ] as well as Mizuno et al [ 50 ] calculated a dimer-geometry where both molecules are stacked with the oxygen atoms in opposite directions. In contrast, Gargano and co-workers [ 48 ] calculated an almost T-like structure. This confirmed the simulations of Bowron et al [ 49 ], which showed that the creation of larger clusters is done by T-like packing of the molecules.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation